Leveraging Agriculture for Improving Nutrition & Health: Addressing Undernutrition in India's Society (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Although tremendous progress has been made in meeting the India’s food demand, still many parts of the country and many sections of the society suffer from under nutrition-that is, deficiencies in energy, protein and essential vitamins and minerals.